(Re)constructing Armenia in Lebanon and Syria : ethno-cultural diversity and the state in the aftermath of a refugee crisis - Migliorino, Nicola (Studies in forced migration, 2008)
For almost nine decades, since their mass-resettlement to the Levant in the wake of the Genocide and First World War, the Armenian communities of Lebanon and Syria appear to have successfully maintained a distinct identity as an ethno-culturally diverse group, in spite of representing a small non-Arab and Christian minority within a very different, mostly Arab and Muslim environment. The author shows that, while in Lebanon the state has facilitated the development of an extensive and effective system of Armenian ethno-cultural preservation, in Syria the emergence of centralizing, authoritarian.